mTOR as a Marker of Exercise and Fatigue in Octopus vulgaris Arm - Maiole, Federica; Giachero, Sarah; Fossati, Sara Maria; Rocchi, Anna; Zullo, Letizia (Frontiers in Physiology, 2019)
Cephalopods are highly evolved marine invertebrates that colonized almost all the oceans of the world at all depths. This imposed the occurrence of several modifications of their brain and body whose muscle component represents the major constituent. Hence, studying their muscle physiology may give important hints in the context of animal biology and environmental adaptability. One major pathway involved in muscle metabolism in vertebrates is the evolutionary conserved mTOR-signaling cascade; however, its role in cephalopods has never been elucidated. mTOR is regulating cell growth and homeostasis in response to a wide range of cues such as nutrient availability, body temperature and locomotion. It forms two functionally heteromeric complexes, mTORC1 and mTORC2. mTORC1 regulates protein synthesis and degradation and, in skeletal muscles, its activation upon exercise induces muscle growth. In this work, we characterized Octopus vulgaris mTOR full sequence and functional domains; we found a high level of homology with vertebrates’ mTOR and the conservation of Ser2448 phosphorylation site required for mTORC1 activation. We then designed and tested an in vitro protocol of resistance exercise (RE) inducing fatigue in arm samples. We showed that, upon the establishment of fatigue, a transient increase in mTORC1 phosphorylation reaching a pick 30 min after exercise was induced. Our data indicate the activation of mTORC1 pathway in exercise paradigm and possibly in the regulation of energy homeostasis in octopus and suggest that mTORC1 activity can be used to monitor animal response to changes in physiological and ecological conditions and, more in general, the animal welfare.